Analysis of the Need for Innovation in Agricultural Land Conversion Prevention Policies in Bengkulu City from a Regulatory Perspective - Ria Sari Putri; Sinta Ningrum; Candradewini Candradewini (International Journal of Science and Society, 2026)
The conversion of agricultural land has become a strategic issue with direct implications for food security, particularly in urban areas experiencing rapid development and population growth. Bengkulu City, as a provincial capital, has also undergone intensive agricultural land conversion. However, to date, no specific local policy has been established to ensure the protection of sustainable food agricultural land. This study examines the role of local regulations in preventing agricultural land conversion while identifying the need for adaptive policy innovations aligned with the local characteristics of Bengkulu City. Data were collected through in-depth interviews with relevant stakeholders, field observations in agricultural areas affected by land conversion, and document analysis of applicable local regulations. Data analysis followed the Miles and Huberman interactive model, reinforced by NVivo-assisted qualitative analysis to identify key themes and regulatory indicators. The findings reveal that the Bengkulu City Government currently relies on Local Regulation No. 4 of 2021 on the Regional Spatial Plan (2021-2041) concerning the Regional Spatial Plan as the primary instrument for controlling agricultural land conversion. Although this regulation normatively establishes spatial zoning, it has not effectively restrained agricultural land conversion due to the absence of specific provisions on the protection of sustainable food agricultural land. NVivo analysis identified three major regulatory indicators: regulations that support innovation, regulations that hinder innovation, and bureaucratic hierarchy. The lack of a specific regulation on Sustainable Food Agricultural Land Protection (LP2B), weak law enforcement, and complex cross-sectoral coordination are the main factors inhibiting policy innovation. This study concludes that ineffective control of agricultural land conversion in Bengkulu City is not caused by regulatory rigidity but by overreliance on general spatial planning policies without supporting technical and innovative derivative regulations. Therefore, this research recommends the formulation of a specific Local Regulation on Sustainable Food Agricultural Land Protection (LP2B) as an adaptive and integrated policy innovation.